Gênese e função social do estado: o estado brasileiro em tempos de crise estrutural do capital - Silva, Monique Maria Rodrigues da (2016)
This work presents the discussion about the genesis and the social role of the State and the Brazilian State against the demands posed by the structural crisis of capital. This paper aims to investigate the particularity of the Brazilian State and the neoliberalism's forms of expression in the country. For this, we resort the Marxian approach to explain the ontological foundations of the State and its configuration as a modern State, resulting from economic transformations that have established the mode of production governed by the reproduction of capital. In this context, we show how liberalism corresponds to the interests of bourgeois society to give the State the theoretical elements that legitimize its actions. From the I. Mészáros analysis, we highlight how is the complementary relationship between the State and capital, essential for the reproduction of capitalist sociability mode. In addition to, we are interested in demonstrate the State dynamism in relation to the interests of reproduction of system. For this, we underline essential elements of the Welfare State, implemented in the cyclical post-crisis period of 1929, and the State guided by neoliberalism, in force since the 1970s when emerges the structural crisis of capital. In this sense, we resort these two models of State as strategies for reversal of the crisis of the capitalist mode of production. From this historical review, we enter in the Brazilian particularity, presenting constituent elements of economic development of that country, which give the direction of their national State. We highlight the Prussian-colonial via as relevant to the Brazilian capitalist development mode and that allowed the historical dependence and subordination of Brazil to the countries of advanced capitalism, fundamental dynamics for the establishment of the capital system. Finally, the discussion approaches the arrival of neoliberalism in this country and the ways in which the Brazilian government has offered to society, highlighting the militarization of social life and, especially, the new welfarism, as ways to try to curb the ever greater effects of the structural crisis the capital.